Pengaruh harga dan promosi terhadap keputusan pembelian sepeda motor honda beat pada CV. Prima Motor Pasirpangaraian (Studi Kasus Masyarakat Desa Rambah Jaya Kabupaten Rokan Hulu) - Adellia Nur Anggraini; Rosmayani Rosmayani (Pelantar Press, 2022)
The purpose of this study is to analyze, find out, and explain the effect of price and promotion on the purchase decision of Honda Beat motorcycles on a CV. Prima Motor Pasirpangaraian (Case Study of Rambah Jaya Village Community, Rokan Hulu Regency). This study used quantitative methods by managing data obtained from the population and a research sample of 100 respondents and 1 PIC dealer CV. Prima Motor and 1 marketing chairman. The type and source of data used in this study were to use secondary data and primary data where data collection was through the dissemination of questionnaires and conducting interviews. Then the data that has been collected by the author identifies and groups data using a descriptive analysis method, namely conducting research from data that has been found in the field. From the results of the study, the price variable was in the agree-on category, the promotion variable was in the agreed category and the purchase decision was in the agreed category. Then from the statistical calculations, there are results where the price and promotion have a significant effect on the purchase decision of the Honda Beat motorcycle on the CV. Prima Motor Pasirpangaraian (Case Study of Rambah Jaya Village Community, Rokan Hulu Regency).